Macronutrient intake and alertness during night shifts – the time interval matters - de Rijk, Mariëlle G.; van Eekelen, Alexander P. J.; Boesveldt, Sanne; Kaldenberg, Elly; Holwerda, Tineke; Lansink, Ceciel J. M.; Feskens, Edith J. M.; de Vries, Jeanne H. M. (Frontiers in Nutrition, 2023)
Background: Working night shifts is associated with higher safety risks due to shift work-related fatigue. Nutrition, especially certain (macro)nutrient compositions, has been suggested to reduce fatigue, however, results of studies are contradictory. This could be explained by differences in the time interval investigated between the consumption of a meal and measurement of cognitive performance. Therefore, this observational study investigated the association between macronutrient intake and objective alertness at different time intervals during the night shift in nurses.Methods: 128 nurses, aged 20-61 years, completed an alertness test (Psychomotor Vigilance Task) during the night shift and a 24-hour dietary recall after the night shift. This was repeated three times, always on the first night shift in a night shift series. The associations between macronutrient intake 0 to 1, 1 to 2, and 2 to 3 hours before the PVT with alertness during the night shift were analyzed through Linear Mixed Models. The basic model was adjusted for age and gender and the adjusted model additionally for BMI, start time of PVT and energy and caffeine intake during the relevant time interval.Results: Protein intake was not associated with objective alertness levels, while fat and carbohydrates intake had opposite associations with objective alertness levels over similar time intervals. Fat intake up to 1 hour prior to the PVT was borderline associated with a longer median reaction time (RT) (ß=9.00 ms/10 g fat, 95% CI: -0.21, 18.20), while a higher carbohydrate intake up to 1 hour prior to the PVT was borderline associated with shorter median RTs (ß=-3.89, 95% CI: -7.85, 0.06).A higher fat intake 2 to 3 hours prior to the PVT was associated with less lapses (log transformed ß=-0.16; 95% CI: -0.31, -0.02), while a higher carbohydrate intake 2 to 3 hours prior to the PVT was associated with more lapses (ß=0.06, 95% CI: 0.01, 0.12).Our results contribute to understanding the association between macronutrient intake, as part of a mixed meal, and alertness levels. Conflicting results from previous studies may probably be due to time differences between macronutrient intake and alertness testing.